Pseudomonas aeruginosa outer membrane adhesins for human respiratory mucus glycoproteins. - Carnoy, C (1994)
The attachment of Pseudomonas aeruginosa to human respiratory mucus represents an important step in the development of lung infection, especially in cases of cystic fibrosis. For this purpose, microtiter plate adhesion assays have been developed and have suggested that nonpilus adhesins of P. aeruginosa are the most important ones for binding to human respiratory mucins. In order to characterize these mucin-binding adhesins, outer membrane proteins (OMP) from two adhesive strains, 1244-NP and PAK-NP, and their poorly adhesive rpoN mutants, 1244-N3 and PAK-N1, were prepared by a mild extraction with Zwittergent 3-14. Mucin-binding adhesins were detected after polyacrylamide gel electrophoresis and blotting of the OMP on nitrocellulose replicas, using human bronchial mucins labeled with 125I. The binding properties of these OMP with lactotransferrin, another glycoprotein abundant in respiratory mucus, were also studied. Radiolabeled mucins detected four bands at 48, 46, 28, and 25 kDa with strain PAK-NP. With the nonmucoid strain 1244-NP, five bands were observed at 48, 46, 42, 28, and 25 kDa. The bands at 48 and 25 kDa were also visualized by radiolabeled lactotransferrin. These bands were partially or completely displaced by nonradiolabeled respiratory mucin glycopeptides but not by tetramethylurea, suggesting that they recognized carbohydrate sites. In contrast, the poorly adhesive strains showed weakly binding bands. These results demonstrate that outer membranes from two different nonpiliated P. aeruginosa strains express multiple adhesins with an affinity for human respiratory mucins and/or lactotransferrin.